2015
DOI: 10.1680/jees.14.00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-heating on microwave enhanced advanced oxidation process

Abstract: Aerobic sewage sludge and dairy manure were pre-treated by conventional heating (CH) (40, 50 and 60°C) followed by microwave enhanced advanced oxidation process (MW/H 2 O 2 -AOP) at 100 and 120°C for solids disintegration and nutrient release. Increasing CH and MW temperatures resulted in an increase in soluble chemical oxygen demand concentration and volatile fatty acids in the treated solution. The maximum ratio of soluble to total chemical oxygen demand obtained for sewage sludge and dairy manure was 60% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…[29] The MW/H 2 O 2 -AOP treatment of the sludge taken from the same MEBPR treatment system earlier (2 years ago) resulted in almost all of the soluble phosphorus being in the form of orthophosphate, and only a small fraction of polyphosphates being present in the microwave-treated solutions. [3,30] Based on our studies and others, it can be concluded that the release of phosphorus was dependent on its existent phosphorus forms in the sludge and EPS. In this study, polyphosphates might consist of elongated polyphosphate chemical bonds, which could not be easily hydrolyzed to form orthophosphate.…”
Section: Nutrient Releasementioning
confidence: 69%
See 3 more Smart Citations
“…[29] The MW/H 2 O 2 -AOP treatment of the sludge taken from the same MEBPR treatment system earlier (2 years ago) resulted in almost all of the soluble phosphorus being in the form of orthophosphate, and only a small fraction of polyphosphates being present in the microwave-treated solutions. [3,30] Based on our studies and others, it can be concluded that the release of phosphorus was dependent on its existent phosphorus forms in the sludge and EPS. In this study, polyphosphates might consist of elongated polyphosphate chemical bonds, which could not be easily hydrolyzed to form orthophosphate.…”
Section: Nutrient Releasementioning
confidence: 69%
“…Similarly, preheating sludge at 40, 50, and 60 8C to deactivate catalase first, the highest SCOD was attained in the preheated solution of 60 8C after subsequent MW/H 2 O 2 -AOP treatment to 100 8C. [3] Catalase enzyme was completely deactivated at 60 8C, and more H 2 O 2 was therefore available for reacting with sludge particulates. [7,8] Set 3 was conducted with the same H 2 O 2 dosage and flow rate as Set 2; however, H 2 O 2 was introduced at 60 8C, instead of being added at the beginning of the experiment.…”
Section: Solids Disintegrationmentioning
confidence: 94%
See 2 more Smart Citations